341OClinical and FDG-PET markers of immune checkpoint inhibitor (ICI) response in patients with metastatic Merkel cell carcinoma (mMCC). (24th November 2019) - Weppler, A M; Bhave, P; Ieso, P De; Chua, M; Raleigh, J; Hatzimihalis, A; Gill, A; Balachander, S; Callahan, J; Pattison, A; Caneborg, A; Yeung, G Au; et al.
Abstract: Background: mMCC is a rare, highly aggressive neuroendocrine cancer of the skin with a poor prognosis. ICIs have favourable efficacy and safety in clinical trials. We outline single centre experience utilising ICIs in mMCC. Methods: Medical records of patients (pts) with mMCC treated with ICIs from Aug 2015 to Dec 2018 at Peter MacCallum Cancer Centre in Australia were retrospectively analysed. RNA sequencing and immunohistochemistry for PD-L1, CD3 and Merkel cell polyomavirus (MCPyV) on tumor samples were performed. Baseline tumor volumes and responses were assessed with FDG-PET scans using the Hicks criteria. Results: 23 pts with mMCC were treated with ICIs. Pt characteristics are summarised in the table. A median of 8 cycles (range 1 to 47) were administered, with treatment ongoing in 6 pts. Objective responses (OR) were observed in 14 pts (61%); 10 (44%) complete metabolic responses (CMR) and 4 (17%) partial metabolic responses (PMR). Median time to response was 8 weeks (range 6 to 12) and 12-month progression-free survival (PFS) rate was 39%. Increased OR were seen in pts aged less than 75 (OR 8/10, 80% vs 46%), pts with normal baseline LDH (OR 5/7, 71% vs 50%), pts with an immune-related adverse event (irAE) (OR 6/6, 100% vs 47%) and in MCPyV negative pts (OR 11/16, 69% vs 43%). Pts with a CMR had lower mean-tumor volume on baseline FDG-PET scan (CMR: 35.7mL, no CMR: 187.8mL, p = 0.05). No correlation was seen between tumor PD-L1 positivity and response to ICI (p = 0.25) or MCPyV status (p = 0.76). Similarly, no association was seen between OR and CD3 staining within the tumor (p = 0.07). 10 pts received radiation (RT) during ICI: 4 pts started RT concurrently (OR 75%, CMR 50%), 3 pts had isolated ICI-resistant lesions successfully treated with RT and 3 pts with multisite progression continued to progress despite RT. 6 pts (26%) had a Grade 1-2 irAE. Conclusions: ICIs showed efficacy and safety consistent with trial data. Younger age, negative MCPyV status, normal LDH, lower baseline FDG-PET tumor volume and irAEs are potentially associated with enhanced response. Legal entity responsible for the study: The authors. Funding: Has not received any funding. Disclosure: R.J. Hicks: Shareholder / Stockholder / Stock options: Telix Pharmaceuticals; Travel / Accommodation / Expenses: Endocyte; Travel / Accommodation / Expenses: GE Medical Systems. R. Tothill: Honoraria (self), Travel / Accommodation / Expenses: Merck Serono. All other authors have declared no conflicts of interest.